Interactions between platelet activating factor and eicosanoids during endotoxic shock in anaesthetized pigs - T. Mózes; F. J. Zijlstra; J. P. C. Heiligers (Hindawi Limited, 1992)
The effects of platelet activating factor (PAF) on eicosanoid release during endotoxic shock was investigated in anaesthetized pigs receiving 5 μg kg−1 Escherichia coli endotoxin (LPS) into the superior mesenteric artery over a 60 min period, by measuring plasma levels of a variety of mediators. Fifteen of the 31 animals infused with LPS and not treated with BN 52021, a PAF receptor antagonist, died within 30 min after the commencement of LPS infusion (non-survivors), while the other 16 survived the experimental period of 3 h, though in a state of shock (survivors). No alterations were observed in plasma concentrations of eicosanoids in the non-survivors. A significant, though transient, increase in eicosanoid concentrations occurred only in the survivors. Treatment with BN 52021 (4 mg kg-1, i.v.) injected 5 min prior to LPS infusion, failed to exert any effect on the survival rate. However, pretreatment with BN 52021 prevented circulatory collapse in the survivors and reduced the concentration of cyclooxygenase enzyme products, without affecting LTB4 release. Exogenous administration of PAF (0.01 μg kg−1) caused hypotension and increased TXB2 levels although 6-keto PGF1α and LTB4 concentrations were unchanged. The data suggest that prostanoid formation may be secondary to PAF release in circulatory collapse evoked by LPS infusion in survivors, and give further support to the suggestion that PAF prostanoid interaction is important during endotoxic shock. However, their role in early death seems to be negligible, indicating the importance of other mediators.